DIGITAL TRANSFORMATION: THE ROLE OF DIGITAL TRANSFORMATION IN COMPANY SUCCESS SYSTEMS - Syahida, Tiara Nurul; Nasution, Muhammad Irwan Padly; Sundari, Sri Suci Ayu (Bina Bangsa International Journal of Business and Management, 2024)
In today's free competition, management information systems play a strategic role in designing good business processes that are the key to the success of an organization / company. The needs of management information systems are highly dependent on the components used to produce such information systems. Gaps in the implementation of this component reduce the accuracy, detail, timeliness and relevance of information, leading to errors in business or organizational decision-making. Therefore, to achieve a sustainable competitive advantage requires a deep understanding of the components of management information systems, especially hardware, software, and brainware. Over time, digital transformation continues to develop to face the revolutions that will develop in the future. The purpose of this study is to find out the role of digital transformation in the success system of the company's sector.